Efficacy of omadacycline in the treatment of Legionella pneumonia: a case report - Wang, Yao; Yi, Shui-Min; Huang, Si-Min; Xu, Wei-Xin; Wei, Yi-Wen; Qu, Qiang; Qu, Jian (Frontiers in Cellular and Infection Microbiology, 2024)
Legionella, one of the main pathogens that causes community-acquired pneumonia, can lead to Legionella pneumonia, a condition characterized predominantly by severe pneumonia. This disease, caused by the bacterium Legionella pneumophila, can quickly progress to critical pneumonia and is often associated with damage to multiple organs.As a result, it requires close attention in terms of clinical diagnosis and treatment.Omadacycline, a new type of tetracycline derivative belonging to the aminomethylcycline class of antibiotics, is a semi-synthetic compound derived from minocycline. Its key structural feature, the aminomethyl modification, allows omadacycline to overcome bacterial resistance and broadens its range of effectiveness against bacteria. Clinical studies have demonstrated that omadacycline is not metabolized in the body, and patients with hepatic and renal dysfunction do not need to adjust their dosage. This paper reports a case of successful treatment of Legionella pneumonia with omadacycline in a patient who initially did not respond to empirical treatment with moxifloxacin. The patient also experienced electrolyte disturbance, as well as dysfunction in the liver and kidneys, delirium, and other related psychiatric symptoms.